Manufacturing technology - Timings, R. L. (Harlow, England : Longman Scientific & Technical, 1992)
A revised second edition, written for the BTEC Standard Unit 1667C: Manufacturing Technology Level "N". It is suitable for students studying for an ONC/OND qualification in engineering and for undergraduate and HNC/HND manufacturing engineering courses, when used in conjunction with volume two.
Includes index
Keywords: Fabrication; Manufacturing industries Technology; Manufacturing processes